2003
DOI: 10.1046/j.1600-0749.2003.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Proliferation and Differentiation of Neonatal Mouse Pink‐Eyed Dilution Melanocytes in the Presence of Excess Tyrosine

Abstract: Changes in the proliferation and differentiation of epidermal melanocytes derived from newborn mice wild-type at the pink-eyed dilution (p) locus (P/P) and from congenic mice mutant at that locus (p/p) were investigated in serum-free primary culture, with or without the addition of L-Tyr. Incubation with added L-Tyr inhibited the proliferation of P/P melanocytes in a concentration-dependent manner and inhibition was gradually augmented as the donor mice aged. In contrast, L-Tyr stimulated the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…, 2003). The dramatic increases in the plasma levels of 6H5MI2C and 5‐ S ‐CD after birth are also consistent with our previous results on the p/p melanocytes (Hirobe et al. , 2003).…”
Section: Plasma Levels Of 6h5mi2c and 5‐s‐cd In Comparison With Melasupporting
confidence: 92%
See 2 more Smart Citations
“…, 2003). The dramatic increases in the plasma levels of 6H5MI2C and 5‐ S ‐CD after birth are also consistent with our previous results on the p/p melanocytes (Hirobe et al. , 2003).…”
Section: Plasma Levels Of 6h5mi2c and 5‐s‐cd In Comparison With Melasupporting
confidence: 92%
“…, 2007). The mouse pink‐eyed dilution ( p ) locus greatly reduces the production of eumelanin in melanocytes and in the retinal pigment epithelium (Hirobe et al. , 2003).…”
Section: Plasma Levels Of 6h5mi2c and 5‐s‐cd In Comparison With Melamentioning
confidence: 99%
See 1 more Smart Citation
“…Also studies on melanoblasts and melanocytes from C57BL/10 mice demonstrated that L‐tyrosine also increases formation of premelanosomes and melanosomes in mutant (pp) melanocytes and increased intracellular concentration of c‐Kit, TyrP1 and TyrP2 protein in both non‐mutant (PP) and pp cells with increased tyrosinase accumulation, as demonstrated by DOPA cytochemistry (Hirobe et al., 2002). Interestingly, L‐tyrosine, while stimulating proliferation of pp melanocytes inhibited growth of PP melanocytes (Hirobe et al., 2003). Furthermore, Hirobe et al.…”
Section: L‐tyrosine and L‐dopa As Positive Regulators Of Melanogenesismentioning
confidence: 99%
“…Also, the synthesis of pheomelanin, consumes cysteine and this may further limit the capacity of the cellular antioxidative defense (Smith et al, 2008). In fact, in cultured normal melanocytes, stimulation of melanogenesis leads to the suppression of proliferation, cell senescence and eventually to cell death (Hirobe et al, 2003). Melanogenesis process generates highly toxic melanin intermediates and byproducts.…”
Section: Cytotoxicity Of Melanins and Their Precursorsmentioning
confidence: 99%